Spór o mangę – rzut oka z perspektywy badacza komiksu - Birek, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article is an attempt to analyse the methods and critical arguments against the manga and anime expressed by the people who, in the polemical discourse of their opponents, are treated as experts. The analysis focuses mostly on articles by Małgorzata Więczkowska, highlighting the constant crypto-self-quotations and the repeating of factual errors and steoreotypical biases. In these texts, one can notice i.e. the generalisation of accusations based on opinions on particular titles, describing the entire phenomenon through the characteristics of selected types and genres, the lack of any distinction being made between manga and anime, and lastly, a superficial understanding of the works in question, whose content and message the author often extrapolates from an overview, without taking the specifics of each work into account.